2012
DOI: 10.1089/dia.2011.0213
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers in Relation to Nonalcoholic Fatty Liver Disease in Urban South Indians

Abstract: hsCRP and leukocyte count are associated with NAFLD after adjusting for conventional cardiometabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Previous studies have demonstrated an association between WBC counts and NAFLD [4, 16]. However, these studies have cross-sectional designs; thus it was impossible to draw strong conclusions regarding the existence of causal relationships between WBC counts and NAFLD or the temporal sequence of events linking the two variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an association between WBC counts and NAFLD [4, 16]. However, these studies have cross-sectional designs; thus it was impossible to draw strong conclusions regarding the existence of causal relationships between WBC counts and NAFLD or the temporal sequence of events linking the two variables.…”
Section: Discussionmentioning
confidence: 99%
“…It encompasses a wide spectrum of histological features that range from simple steatosis to severe forms of fibrosis, steatohepatitis and even cirrhosis. [1][2][3] Its pathogenesis is not completely understood, but several abnormalities have been strongly linked to its onset, such as central obesity, insulin resistance, chronic inflammation, increased uptake of fatty acids by the liver and lipotoxicity. 4,5 NAFLD has been considered to be a hepatic manifestation of metabolic syndrome (MetS) and, as such, is strongly related to type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, 1 mg/l increase in hs-CRP was shown to increase the risk of NAFLD by 1.7 times. Increased levels of other pro-inflammatory cytokines in AsianIndians with NAFLD have been shown in various studies 36,37 . …”
Section: Subclinical Inflammationmentioning
confidence: 89%